Kinerja Pelayanan Penyuluh dan Kompetensi Petani dalam Usahatani Jagung Di Desa Lapodidi Kecamatan Kontunaga Kabupaten Muna - Agustin, Amellya; Rela, Iskandar Zainuddin; Lasinta, Megafirmawanti (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The aims of this study were (1) to determine the performance of extension services in increasing the competence of farmers in corn farming in Lapodidi Village, Kontunaga District, Muna Regency, and (2) to determine the level of competence of farmers in corn farming in Lapodidi Village, Kontunaga District, Muna Regency. This research was conducted from December 2022 to January 2023, and the study population was all corn farmers in Lapodidi Village, totaling 85 people. The data analysis used in this study is a quantitative descriptive analysis. The results showed that (1) the performance of extension services in Lapodidi Village, Kontunaga District, Muna Regency included physical (tangible) services, included in the high category with an average of 4.36, Reliability was included in the high category with an average of 4, 11, responsiveness is included in the high category with an average of 4.44, assurance is included in the high category with an average of 4.23 and empathy is included in the high category with an average of 4.44. This data shows that the performance of extension services in Lapodidi Village is included in the high category, and the performance of extension services has been well implemented. (2) The competence of farmers in Lapodidi Village, Kontunaga District, Muna Regency consists of knowledge included in the high category with an average of 4.08 and skills included in the medium category with an average of 3.66. The knowledge of farmers in Lapodidi Village is quite good, but the skills of farmers need to be improved.